2020
DOI: 10.12688/f1000research.22909.1
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of intravenous nefopam after spine surgery: a randomized, double-blind, placebo-controlled trial

Abstract: Background: The incidence of moderate to severe pain is high among patients undergoing spinal surgery. Nefopam can be used as an adjuvant analgesic postoperatively after spine surgery. The study aimed to assess the analgesic efficacy and side effects of nefopam on 24-hour postoperative morphine consumption after spine surgery. Methods: The study is a randomized, double-blinded, placebo-controlled trial. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Regarding spine surgery, a recent study in patients undergoing open spine surgery receiving intravenous nefopam administered before skin incision and before the end of the operation demonstrated similar morphine consumption and postoperative pain compared to those in the placebo group [11]. Our study showed the same results, namely, there was no additional analgesic effect of nefopam despite its continuous infusion for 24 hours after the operation.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding spine surgery, a recent study in patients undergoing open spine surgery receiving intravenous nefopam administered before skin incision and before the end of the operation demonstrated similar morphine consumption and postoperative pain compared to those in the placebo group [11]. Our study showed the same results, namely, there was no additional analgesic effect of nefopam despite its continuous infusion for 24 hours after the operation.…”
Section: Discussionsupporting
confidence: 78%
“…Adding perioperative nefopam to opioid analgesic does not improve analgesic efficacy in patients who underwent spine surgery. This project contains definitions used in the above dataset 27 . The sample size calculation is unclear:…”
Section: Resultsmentioning
confidence: 99%
“…Pain score and total intraoperative morphine for four treatment groups were not different ( Table 2 ). All raw data are available from Figshare 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conflicting results have also been reported, especially in surgeries anticipated to cause moderate to severe pain [ 24 , 25 , 26 , 27 ]. Cuvillon et al reported that continuous intravenous infusion of nefopam (120 mg) during the first 48 h after open colectomy did not reduce perioperative opioid consumption and produced no differences in patient satisfaction or adverse events compared with the control group [ 24 ].…”
Section: Discussionmentioning
confidence: 99%